Jack H. Driberg: A Humanistic Anthropologist before His Time - Schmidt, Nancy J. (Anthropologica, 2022)
Jack H. Driberg (1888-1946), a British social anthropologist who wrote a classical ethnography on the Lango before receiving formal anthropological training, spent over a dozen years doing field work in Africa. He was both an atypical colonial administrator who was able to understand and convey to others Africans’ views and an extraordinary anthropologist for his time and place who raised issues in anthropology which have come to the fore only in recent years, primarily in American humanistic anthropology. This essay reassesses Driberg’s contributions to humanistic anthropology focusing on his writing in "non-scientific" genres.